Perceptions of Use Patterns and Health Consequences Associated With Mentholated Cigarettes Among U.S. Adults. (April 2020) - Glasser, Allison M.; Barton, Alexis; Rath, Jessica; Simard, Bethany; Rose, Shyanika W.; Hair, Elizabeth; Vallone, Donna
Despite declines in overall cigarette smoking in the United States, menthol cigarette smoking prevalence has increased among young adults (18-25 years) and remains constant among older adults (26 years and older). Disparities in menthol cigarette use exist, with higher prevalence among younger adult smokers and among racial/ethnic minority populations. Menthol in cigarettes has been shown to play a role in increasing smoking initiation and making it more difficult to quit smoking. Little research focuses on perceptions of the addictive potential and health consequences of menthol cigarette use. This analysis uses data from a national panel of U.S. adults ( n = 1, 303) surveyed in 2016. Participants were asked to what extent they agreed with various statements regarding menthol use among demographic and tobacco use subgroups. These data reveal disparities in perceptions of the impact of menthol use, with Black, non-Hispanic, and Hispanic adults and adults with lower income and less education misperceiving the health effects and addiction potential of menthol in cigarettes. Determining how and to what extent population subgroups understand the effect of menthol cigarette use can inform public education strategies and, in turn, policy efforts to ban or restrict menthol cigarette availability.